Description of stratification phenomena in the fluid reservoirs with first-order chemical reaction. (April 2019) - Jabeen, Iffat; Farooq, Muhammad; Mir, Nazir Ahmad
In real life applications, summer and winter stratifications prevent the fluid from mixing. This phenomenon has great impact on the phytoplankton (algae) populations, fisheries management and water supply quality, deficiency of dissolved oxygen in the lower region of ponds, lakes and rivers. Thus, our main moto in this article is to highlight the features of mixed convection in Powell–Eyring fluid deformed by an inclined stretchable sheet. Characteristics of heat transfer are exposed via thermal stratification. The solutal stratification and chemical reaction of first order are accounted to elaborate the nature of mass transfer. The coupled non-linear equations with ordinary derivatives are acquired after utilizing suitable transformation. The homotopic approach is adopted to accomplish the convergent series solution. Analysis of various emerging parameters on the fluid's temperature, velocity and concentration fields is elaborated through graphs. Surface drag, Sherwood and Nusselt numbers are studied through graphical data corresponding to numerous parameters. In conclusion, dominant solutal and thermal stratified parameters are responsible for reduction of concentration and temperature fields, respectively, which enables us to prevent the formation of fluid layers with different density regions.